Teachers' training and the use of educational technologies: research results - Marina Chiaro (Firenze University Press, 2016)
Acquire technological skills is an important requirement clearly evident by teachers in primary and secondary school at the end of a blended training course held at the University of Rome Three about issues related to students with Learning Disabilities. It is also significant the chance for teachers to constitute professional communities, such as the Community of Practice in the Lifelong Learning perspective, that might lead to collaborative strategies, knowledge sharing, discussion and reflection that are necessary to face the difficulties that every innovation involves. These factors can help teachers to overcome the condition of isolation which represents an important barrier to the development of an inclusive school in order to design inclusive educational strategies with the use of Information and Communication Technology according to the cultural perspective of the International Classification of Functioning, Disability and Health for Children and Youth. Formazione degli insegnanti ed impiego delle tecnologie didattiche per l'inclusione: risultati di ricerca Acquisire competenze tecnologiche rappresenta una importante esigenza palesata da docenti in servizio nella scuola primaria e secondaria di I e II grado al termine di un percorso formativo svolto in modalità blended presso l'Università degli Studi di Roma Tre su tematiche relative agli allievi con Disturbi Specifici di Apprendimento. Rilevante anche la possibilità per gli insegnanti di costituire delle comunità professionali, quali le Comunità di Pratica, in ottica di lifelong learning, che possano dar luogo a strategie collaborative, di condivisione delle conoscenze, di confronto e riflessione necessari per affrontare le difficoltà che ogni innovazione comporta. Tali modalità possono rappresentare un supporto al superamento della condizione di isolamento in cui spesso i docenti si trovano ad operare, aspetto che costituisce uno dei principali ostacoli allo sviluppo di una scuola efficace ed inclusiva finalizzata anche alla possibilità di progettare strategie didattiche inclusive con il supporto dell'Information and Communication Technology secondo la prospettiva culturale della International Classification of Functioning, Disability and Health for Children and Youth.